THE INFLUENCE OF THE PERSONAL DATA PROTECTION LAW (UU PDP) ON LAW ENFORCEMENT IN THE DIGITAL ERA - Bintarawati, Fenny (PT. Altin Riset Publishing, 2024)
Objective study This study examines the influence of the Constitution personal data protection (PDP) law against law enforcement in the digital era. Method used is method study qualitative with type study studies. References . Types of studies References used for digging deep understanding about a topic or phenomenon with an analysis of literature and where are the relevant sources? in study This related influence of the Constitution personal data protection (PDP) law against law enforcement in the digital era. As for the data, it was obtained through study and analysis of various references, like journals, scientific articles, and documents related to the topic being researched. Then, the researcher read an interesting thread and concluded from the results, findings, and study. Results study This leads to the conclusion that complexity influences Constitutional Personal Data Protection and enforcement law in the digital era. Even though the PDP Law provides an important basis, the challenges and dynamics faced need a planned response and coordination from the government, private sector, and public. Overcome problem enforcement The PDP Law in the digital era requires effort, collaboration, and solutions integrated from party authority, sector private, community, and holder interests. With a thorough understanding of the problem, an effective strategy can be developed to ensure that personal data protection remains a top priority in the ever-expanding digital world.